2014
DOI: 10.1007/s11011-014-9559-7
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral hemorrhage in mouse models: therapeutic interventions and functional recovery

Abstract: There has been strong pre-clinical research on mechanisms of initial cell death and tissue injury in intracerebral hemorrhage (ICH). This data has led to the evaluation of several therapeutics for neuroprotection or the mitigation of early tissue damage. Most of these studies have been done in the rat. Also, there has been little study of the mechanisms of tissue repair and recovery. This review examines the testing of candidate therapeutics in mouse models of ICH for their effect on tissue protection and repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 97 publications
(104 reference statements)
0
12
0
Order By: Relevance
“…clot-derived cytotoxic factors, neuroinflammation 1113 ) injury components followed by a period of repair. The therapeutic time window for modulating brain repair may be longer than for preventing ICH-induced brain injury 14 .…”
Section: Modeling Ich-induced Brain Injury and Repair – Areas For Focusmentioning
confidence: 99%
“…clot-derived cytotoxic factors, neuroinflammation 1113 ) injury components followed by a period of repair. The therapeutic time window for modulating brain repair may be longer than for preventing ICH-induced brain injury 14 .…”
Section: Modeling Ich-induced Brain Injury and Repair – Areas For Focusmentioning
confidence: 99%
“…Compounds currently under study include such drugs as deferoxamine, minocycline, statins, celecoxib, desmopressin, and conivaptan. These drugs each addresses some aspect of the pathology noted in the mechanisms above [ 32 , 34 , 35 ]. Similar to stroke and thrombectomy in the past, advances in ICH treatment have been stalled by a lack of significant positive data supporting evacuation/removal of the hematoma.…”
Section: Conference Proceedings—october 4–5 2017mentioning
confidence: 99%
“…Intracerebral hemorrhage (ICH) accounts for about 15% of all strokes, with 1-month mortality rates of 50% in patients after ICH [1]. Previous studies have demonstrated that the Blood–Brain barrier (BBB) integrity was disrupted in brain damage after ICH, leading to neurological deficits, inflammatory responses, and cerebral edema [2,3]. The BBB consists of endothelial cells (ECs), pericytes, astrocytes, neurons, and the extracellular matrix (ECM) [4].…”
Section: Introductionmentioning
confidence: 99%